Depth‐Dependent Thermal Stress Around Corals in the Tropical Pacific Ocean. Issue 18 (21st September 2018) - Schramek, T. A.; Colin, P. L.; Merrifield, M. A.; Terrill, E. J.
Abstract: Thermally driven bleaching events are a growing concern for reef ecosystems across the tropics. To assess and predict thermal stress impacts on reefs, remotely observed sea surface temperature (SST) commonly is used; however, reef communities typically extend to depths where SST alone may not be an accurate measure of in situ variability. Here nearly two decades of temperature observations (2‐ to 90‐m depth) at three stations around Palau are used to develop an empirical model of temperature variability versus depth based on SST and sea level anomaly (SLA). The technique yields depth‐averaged R 2 values >0.88, with SLA predicting fore reef temperatures near the thermocline and SST capturing upper mixed layer temperatures. SLA complements SST by providing a proxy for vertical isotherm displacements driven by local and remote winds on intraseasonal to interannual time scales. Utilizing this concept, thermal stress on corals can be predicted from the surface through the mesophotic zone. Plain Language Summary: Coral reefs are often bleached, leading to their death, due to exceedingly warm ocean temperatures. The temperature of the ocean's surface, measured globally by satellites, is often used as an indicator of the temperature and stress that corals experience, but it can only tell us what is happening near the surface. We present nearly two decades of temperature records from the reefs of Palau, an island nation in the tropical Pacific. This array of instruments was maintained by skilled divers routinely going deeper than 90 m. The observations allow us to show that the height of the ocean surface is a strong indicator of how ocean temperatures are changing tens of meters below. This can be coupled with observed sea surface temperature to predict the temperatures experienced by coral reefs living near the surface as well as those living deeper, down through the mesophotic zone, an area between 30 and 150 m deep. The research suggests that significant improvements can be made to how temperature stress on corals is assessed. We also find that thermal stress events can penetrate into the realm of deep mesophotic coral reefs, meaning that this zone might not be refugia for corals living in a warming ocean. Key Points: Fore reef temperature in the tropics can be reconstructed with sea level and sea surface temperatures in multiple linear regressions Sea surface temperature sets the temperature of the upper mixed layer, while sea level indicates temperatures near the thermocline Thermal stress metrics can be adapted for mesophotic coral ecosystems by accounting for the variability in temperature near the thermocline